EXPLORING THE IMPACT OF DEBATES SUPPORTED BY ARTIFICIAL INTELLIGENCE: INNOVATIVE STRATEGIES TO EMPOWERING SCIENTIFIC ARGUMENTATION SKILLS IN BIOLOGY CLASSES - Resi, Damasus Nosi; Sutarno, Sutarno; Indrowati, Meti (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2026)
Scientific argumentation is a key skill and an important variable that plays a central role in biology learning, which in practice has not been well trained. The purpose of this study was to determine the effect of debate activities supported by artificial intelligence as a tool to improve students' scientific argumentation skills. This study adopts a quantitative descriptive method by integrating a quasi-experimental approach. The research sample consists of 72 tenth-grade students from State High School 7 Surakarta, divided into experimental and control groups. A scientific argumentation test instrument in the form of essay questions was used to analyze the final synergistic effect of the intervention provided. The research findings indicate that there are significant differences between the control and experimental groups in certain elements, both in terms of argumentation structure criteria (Claims and Data) and argumentation quality criteria (Organization, Sufficiency, and Clarity) with a p-value 0.05, indicating that AI-supported debates only influence initial elements, thus concluding that they are not yet effective across all elements of scientific argumentation skills. This highlights the need for sufficient time and more targeted instruction to maximize the development of students' scientific argumentation skills.